VISUALIZING TRANSPARENCY: THE ROLE OF VIRTUAL SCHOOL TOURS IN STRENGTHENING INSTITUTIONAL ACCOUNTABILITY AND STAKEHOLDER TRUST - Abu Yazid Albustomi; Hasan Baharun; Annisa Tri Ananda Dewi; Moses Adeleke Adeoye (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study aims to analyze the meaning of virtual tours as a form of transparency in school facilities and their role in building institutional accountability and stakeholder trust. The study used a qualitative approach with a case study design. Data were collected through in-depth interviews with the principal, vice principal for facilities and infrastructure, teachers, public relations staff, and parents of students, along with observations of the content of the school's virtual tours. Data analysis was conducted thematically through a process of reduction, presentation, and conclusion drawing. The results show that virtual tours are interpreted as a practice of openness that displays the condition of school facilities visually, as they are, and easily accessible to the public. Visual transparency serves to reduce information gaps, strengthen perceptions of honesty, and build parental trust from the initial stage of interaction. Furthermore, virtual tours contribute to strengthening school relations with stakeholders and encouraging improvements in internal facility governance. The implications of this study emphasize the importance of using digital technology as an instrument of transparency and accountability in educational management.